Effect of Ducrosia anethifolia methanol extract against methicillin resistant Staphylococcus aureus and Pseudomonas aeruginosa biofilms on excision wound in diabetic mice - Almuhanna, Yasir (Frontiers in Cellular and Infection Microbiology, 2024)
Background Ducrosia anethifolia is an aromatic desert plant used in Saudi folk medicine to treat skin infections. It is widely found in Middle Eastern countries. Methods A methanolic extract of the plant was prepared, and its phytoconstituents were determined using LC-MS. In-vitro and in-vivo antibacterial and antibiofilm activities of the methanolic extract were evaluated against multidrug-resistant bacteria. The cytotoxic effect was assessed using HaCaT cell lines in-vitro. Diabetic mice were used to study the in-vivo antibiofilm and wound healing activity using the excision wound method. Results More than 50 phytoconstituents were found in the extract after LC-MS analysis. The extract exhibited antibacterial activity against both the tested pathogens. The extract was free of irritant effects on mice skin, and no cytotoxicity was observed on HaCaT cells with an IC50 value of 1381 µg/ml. The ointment formulation of the extract increased the healing of diabetic wounds. The microbial load of both pathogens in the wounded tissue was also reduced after the treatment. The extract was more effective against methicillin-resistant Staphylococcus aureus (MRSA) than MDR-P. aeruginosa in both in vitro and in vivo experiments. Further, skin regeneration was also observed in histological studies. Conclusions The results showed that D. anethifolia methanol extract supports wound healing in infected wounds in diabetic mice through antibacterial, antibiofilm, and wound healing activities.